Substantial uptake of atmospheric and groundwater nitrogen by dune slacks under different water table regimes - Rhymes, J.; Wallace, H.; Tang, S. Y.; Jones, T.; Fenner, N.; Jones, L. (Journal of coastal conservation, 2018)
Dune slacks are biodiverse seasonal wetlands which experience considerable fluctuations in water table depths. They are subject to multiple threats such as eutrophication and climate change, and the interactions of both of these pressures are poorly understood. In this study we measured the impact of groundwater nitrogen contamination, as ammonium nitrate (0, 0.2, 10 mg/L of DIN, dissolved inorganic nitrogen), lowered water table depth (lowered by 10 cm) and the interactions of these factors, in a mesocosm study. We measured gross nutrient budgets, evapotranspiration rates, the growth of individual species and plant tissue chemistry. This study found that nitrogen uptake within dune slack habitats is substantial. Atmospheric inputs of 23 kg ha⁻¹ yr.⁻¹ were retained by the mesocosms, with no increase of nutrient levels in the groundwater, i.e. there was no leaching of excess N. When N was added to the groundwater (in addition to atmospheric N), total uptake was equivalent to 116 kg ha⁻¹ yr.⁻¹, at a groundwater DIN concentration of 10 mg/L. This resulted in increased plant tissue N concentrations showing uptake by the vegetation. The effect of lowering water tables did not influence N uptake, but did alter vegetation composition. This suggests that groundwater can be a substantial input of N to these habitats and should be considered in combination with atmospheric inputs, when assessing potential ecosystem damage.